Strategi Penguatan Corporate Branding Badan Kepegawaian Negara (BKN) sebagai Katalisator Kerja Sama Nasional dan Internasional - Sari, Rohmah Nia Chandra (Tuturlogi: Journal of Southeast Asian Communication, 2026)
This study aims to examine the strategy of strengthening corporate branding of the National Civil Service Agency (Badan Kepegawaian Negara) as an effort to strengthen cooperation at the national and international levels. Corporate branding in public organizations is an important instrument in building institutional image, increasing public trust, and expanding national and international collaboration networks. This study uses a thematic research approach by examining branding elements that can be applied such as strengthening visual identity, strategic communication and utilization of digital media. The results of this study indicate that BKN implements various branding strategies, such as strengthening visual identity, optimizing digital media and consistent institutional narratives. Effective corporate branding contributes to the formation of a positive image of BKN. In addition, it opens up opportunities for broad cooperation with national and international partners.